(untitled) (Research, Society and Development, 2024)
The study of anatomy plays a very important role in the evolution of medicine throughout history, since the work of the first anatomists, and has been accompanied by several technological advances. The objective of this research is to analyze the current panorama of anatomical study, technological progress, and the essential foundations of this discipline, in addition to understanding part of the evolutionary trajectory of study methods. For this, an integrative review was carried out using a qualitative approach, with research in databases based on the guiding question “How is the study of anatomy currently carried out?”, using the “PICo” strategy, proceeded A search was carried out in the Embase, PubMed, LILACS and Scopus databases, where a total of 770 studies were found, which were subjected to the inclusion and exclusion criteria, leaving 36, of which 28 were selected for full reading and writing. of this review. From the results obtained, it was observed that the use of cadavers continued, but with the advent of new techniques, such as plastination and virtual dissection. As a conclusion of this study, it is understood that these new methodologies, although they represent significant advances, do not fully replace traditional teaching methods, but rather complement anatomical education.